Korelasi antara Keterlaksanaan Model Treffinger Berbantuan iSpring Suite 8 dengan Kemampuan Berpikir Kreatif - Erma Johar; syamsurizal syamsurizal; Afrida Afrida; Aulia Sanova (Universitas Pendidikan Mandalika Mataram, 2022)
Students only listen and receive lessons from the teacher in online and offline learning activities. The Treffinger model is oneeof the learninggmodels that can help improve creative thinking skills during online or offline learning. The purpose of this study is to determineethe implementationnof the Treffinger model and its relationship to creativeethinkinggskills. This study used three syntaxes for each model: basic tools, process practice, and working with real problems. The study's subjects were 18 students from class XI IPA 4 SMAN 2 Jambi City, and the data sources were students, teachers, and student activities. Interviews, teachereobservation sheets, student observation sheets, and tests were used to collecttdataafor the study, which was then analyzed using qualitative descriptive techniques. The average value of the model's application by students at meetings 1, 2, and 3 is 36.94, 57.02, and 59.15, respectively, indicating an increase in implementation of this learning model. This is consistent with the test results of students' creative thinking abilities, which improve with each meeting, as evidenced by the average value of each successive meeting, which is as follows: 36.11, 46.11, and 48.33 The study concluded that there is there is a correlation between the implementation of the Treffinger model and the creative thinking ability of students in class XI IPA 4 SMAN 2 Jambi City.